Hierarchical capacity management and load balancing for HetNets using multi-layer optimisation methods. (13th July 2022) - Rad, Khodadad Jalali; Mirzaei, A.
This paper proposes a dynamic optimisation model which maximises the overall network capacity of IoT-based heterogeneous networks in addition to providing the essential coverage and capacity. In this paper, we propose a multi-layer optimisation approach based on the optimal transmission strategy to allocate replicas to the IoT data in the cloud computing environment in order to mitigate the data access cost. The proposed algorithm was also employed to determine the best location for data replication in the cloud computing environment. Based on the fundamental trade-off between spectral efficiency and ergodic capacity, we study the joint spectral efficiency and resource optimisation problem in cellular IoT networks with small cells on/off control. Extensive simulation results prove that the proposed approach is able to achieve a better trade-off between spectral efficiency and total ergodic capacity with lower outage probability compared with the existing algorithms under various scenarios.